2014
DOI: 10.1038/ki.2013.518
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin requires the angiotensin II type 2 receptor to abrogate renal interstitial fibrosis

Abstract: Fibrosis is a hallmark of chronic kidney disease, for which there is currently no effective cure. The hormone relaxin is emerging as an effective antifibrotic therapy; however, its mechanism of action is poorly understood. Recent studies have shown that relaxin disrupts the profibrotic actions of transforming growth factor-β1 (TGF-β1) by its cognate receptor, relaxin family peptide receptor 1 (RXFP1), extracellular signal-regulated kinase phosphorylation, and a neuronal nitric oxide synthase-dependent pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
154
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(169 citation statements)
references
References 51 publications
14
154
0
1
Order By: Relevance
“…This is consistent with the view that the agonist most likely mediates its actions by influencing post-receptor signalling pathways. Indeed, recent studies have demonstrated that AT 2 R inhibits AT 1 Rmediated effects by targeting its downstream effectors, including TGF-β1 [41] and NOX [29], as well as its ability to activate vasoconstriction inhibiting factor, an endogenous co-factor of Ang II [42]. Moreover, with previous studies demonstrating that AT 2 R forms a heterodimer receptor complex with AT 1 R to block the signalling and mediated functions of the latter [43], it is possible that some of the Based on our findings that C21 exhibits similar antiatherogenic efficacy as candesartan and that the effects of candesartan could be inhibited in the presence of the AT 2 R antagonist PD123319, this could indicate that candesartanmediated actions occur at least in part as a result of the unopposed action of the AT 2 R. Consistent with these findings are studies, albeit in the non-diabetic setting, where candesartanmediated reduction of infarct size in pigs [44] and inhibition of cardiac remodelling in rats [45] were found to be dependent on AT 2 R activation.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the view that the agonist most likely mediates its actions by influencing post-receptor signalling pathways. Indeed, recent studies have demonstrated that AT 2 R inhibits AT 1 Rmediated effects by targeting its downstream effectors, including TGF-β1 [41] and NOX [29], as well as its ability to activate vasoconstriction inhibiting factor, an endogenous co-factor of Ang II [42]. Moreover, with previous studies demonstrating that AT 2 R forms a heterodimer receptor complex with AT 1 R to block the signalling and mediated functions of the latter [43], it is possible that some of the Based on our findings that C21 exhibits similar antiatherogenic efficacy as candesartan and that the effects of candesartan could be inhibited in the presence of the AT 2 R antagonist PD123319, this could indicate that candesartanmediated actions occur at least in part as a result of the unopposed action of the AT 2 R. Consistent with these findings are studies, albeit in the non-diabetic setting, where candesartanmediated reduction of infarct size in pigs [44] and inhibition of cardiac remodelling in rats [45] were found to be dependent on AT 2 R activation.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between RAS and the relaxin family peptide system have been reported in organ fibrosis (9), blood pressure, in the cardiovascular system (10,11), and osmoregulation, for the central nervous system (12,13) but so far, never in the carcinogenesis of reproductive tissues. However, this study is the first to present the influence of the combined action of angiotensin II and relaxin 2 on various aspects of prostate cancer development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Overactivation of RAS stimulates the proliferation of renal mesangial cells and interstitial fibroblasts, increases the synthesis and secretion of inflammatory factors by renal inherent cells, and promotes the morphological and functional remodeling of cells [6][7][8][9][10][11] . Because angiotensin II (Ang II) is the major effector in RAS, angiotensin-converting enzyme inhibitors (ACEI) and Ang II type I receptor blockers (ARB) are currently recommended as the first-line medications for the treatment of CKD.…”
Section: Introductionmentioning
confidence: 99%